Identifikasi Keterlambatan Pengiriman Produk di PT X pada Departemen Material Preparation Control - Felicia Yanto (Jurnal Titra, 2018)
PT X is a plastic packaging compay. Delay problem at PT X reach 31.4% of total delivery. The purpose of this research is to find the cause of the delay that happened in Material Preparation Control Department at PT X. The causes of the delay classified into two, there are start and process late. The root cause searched by 5-Whys method. The root causes of the late are human eror, machine capacity different between MPC and IMM-EBM, and production faltered. The proposed solutions are periodically checking and MPC production process calculated by Planner is adjusted to the capacity of IMM and EBM machine.